The Application of Indirect Proof Methods to Independent Money Laundering Crimes - M. Arief Amrullah (Jurnal Cakrawala Hukum, 2026)
The study in this article aims to find a solution to the problem of the concept of independent money laundering as stipulated in Article 69 of the Money Laundering Crime Law, especially related to the phrase "it is not mandatory to prove the original criminal act" (predicate crime), which is still the subject of debate among legal experts in Indonesia. In the Netherlands, in dealing with such problems, such problems are solved through the indirect method of proof. Money laundering suspects can be held criminally liable without first having to prove the original criminal act, the most important thing is that there is sufficient evidence that the assets obtained do not come from a legitimate source. This method of indirect proof is used, especially in cases where there is no direct indication of the original criminal act related to the object. Therefore, to support law enforcement against the phrase "it is not mandatory to first prove the original criminal act", it is very important to examine the application of the indirect proof method to the formulation of Article 69 of the Money Laundering Crime Law Art.